Beate Kutschke and Barley Norton (eds), Music and Protest in 1968 (2013) - Robb, David (Journal of the Society for Musicology in Ireland, 2016)
A review of Beate Kutschke and Barley Norton (eds), Music and Protest in 1968 (Cambridge: Cambridge University Press, 2013). ISBN 978-1-107-00732-1